Farmers' knowledge and practices of potato disease management in Ethiopia. (1st November 2018) - Tafesse, Shiferaw; Damtew, E.; van Mierlo, B.; Lie, R.; Lemaga, B.; Sharma, K.; Leeuwis, C.; Struik, P.C.
Abstract: Effective management of potato diseases such as bacterial wilt and late blight depends to a large extent on farmers' knowledge of the diseases as well as on the integration of recommended management methods in their daily practices. Late blight has continued to be a dominant potato disease for many decades in Ethiopia, whereas bacterial wilt has emerged more recently with a devastating impact on the country's potato production systems. A survey of 261 randomly selected farmers was carried out in three major potato growing districts in the central highlands of Ethiopia to examine farmers' knowledge and management practices of the two diseases, and to analyze the role of relevant knowledge in their practices. Considering their different characteristics, three groups of farmers were distinguished: producers of quality declared seed, producers of normal seed and producers of ware. The study shed light on the vital role the lack of knowledge about the diseases plays in shaping farmers' daily potato production practices. Most farmers could recognize symptoms of the diseases on infected leaves and stems. However, they had very limited knowledge of the diseases including their causal agents, spreading mechanisms, and effective management methods, although they knew a little bit more about late blight than about bacterial wilt. Therefore, to effectively manage the diseases, farmers need to learn about the diseases and how to manage them in their local context applying a feasible combination of management options through a community-based approach. The effectivity of such an approach could be enhanced by stipulating operational standards in bylaws and through continuous monitoring of changes in farmers' practices and environmental monitoring for disease occurrence by leveraging an interactive mobile-based platform.